Elevated levels of ingested plastic in a high Arctic seabird, the northern fulmar (Fulmarus glacialis) - Trevail, Alice M.; Gabrielsen, Geir W.; Kühn, Susanne; Van Franeker, Jan A. (Polar biology, 2015)
Plastic pollution is of worldwide concern; however, increases in international commercial activity in the Arctic are occurring without the knowledge of the existing threat posed to the local marine environment by plastic litter. Here, we quantify plastic ingestion by northern fulmars, Fulmarus glacialis , from Svalbard, at the gateway to future shipping routes in the high Arctic. Plastic ingestion by Svalbard fulmars does not follow the established decreasing trend away from human marine impact. Of 40 sampled individuals, 35 fulmars (87.5 %) had plastic in their stomachs, averaging at 0.08 g or 15.3 pieces per individual. Plastic ingestion levels on Svalbard exceed the ecological quality objective defined by OSPAR for European seas. This highlights an urgent need for mitigation of plastic pollution in the Arctic as well as international regulation of future commercial activity.